AKTIVITAS SUPEROKSIDA DISMUTASE TIKUS DIABETES YANG DIBERI EKSTRAK BATANG KAPULAGA DAN GLIBENKLAMID - Gisti Rahmawati; Farida Nur Rachmawati; Hery Winarsi (Fakultas Biologi | Universitas Jenderal Soedirman, 2014)
Superoxide Dismutase (SOD) is an antioxidant enzyme which reduce anion superoxide radicals as well as known caused of diabetes. There are many natural additive was believed having capacity to repaired an antioxidant celluler status. Cardamom’s stem were reported containing flavonoid and vitamin C which have been proven as in vitro antioxidant. There was no data showing its in vivo potency. This study aims to knoe the SOD activity of diabetes rats which were given cardamom stem extract (CSE) and glibenclamide. The research carried out with the use of experimentally Randomized Design Complete (RAL) by administering treatment on diabetes rat without CSE and glibenclamide as a control, consist of 100 mg/kg bodymass CSE and 2 mg/kg bodymass glibenclamide. The experiment consists of 3 treatments with 7 repetitions, blood sampling carried out experiments as much as 3 times with intervals of 7 days once. The data was analyzed using a variety of analysis (ANOVA). The result showed that the SOD activity increased from 4261 Unit/mg protein to 6604,668 Unit/mg protein (P<0.01) in diabetes rats treatment by CSE for 14 days.